Strategi Rekrutmen Pendidik dan Tenaga Kependidikan dalam Penempatan Kerja di MAN 2 Sijunjung - Jamilus, Jamilus; Alwis, Dona Ana Yori (Indo-MathEdu Intellectuals Journal, 2024)
This article investigates various strategies used in the recruitment of educators and education personnel for effective job placement. This study used a qualitative approach with a descriptive method. The subjects of the study were selected using purposive sampling techniques. Data collection is carried out directly through observation and interviews. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. The results show that diverse approaches have been used by educational institutions and organizations to attract qualified individuals into these educational roles. An effective recruitment strategy is not just about finding academically qualified candidates, but also about considering the cultural fit and values of the organization. This article also discusses challenges in the recruitment of educators and education personnel, such as job market competition and changes in education trends. A holistic and continuous approach in the development of recruitment strategies that can adapt to the changing dynamics in the world of education and the job market. This research is in the form of interviews, literature studies, where the author collects data from various references such as books, and scientific articles.